Selective chemical reagents to investigate the role of caspase 6 in apoptosis in acute leukemia T cells. Issue 9 (25th January 2023) - Groborz, Katarzyna M.; Kalinka, Małgorzata; Grzymska, Justyna; Kołt, Sonia; Snipas, Scott J.; Poręba, Marcin
Abstract : Activated effector caspases 3, 6 and 7 are responsible for cleaving a number of target substrates, leading to the ultimate destruction of cells via apoptosis. Abstract : Activated effector caspases 3, 6 and 7 are responsible for cleaving a number of target substrates, leading to the ultimate destruction of cells via apoptosis. The functions of caspases 3 and 7 in apoptosis execution have been widely studied over the years with multiple chemical probes for both of these enzymes. In contrast, caspase 6 seems to be largely neglected when compared to the heavily studied caspases 3 and 7. Therefore, the development of new small-molecule reagents for the selective detection and visualization of caspase 6 activity can improve our understanding of molecular circuits of apoptosis and shed new light on how they intertwine with other types of programmed cell death. In this study, we profiled caspase 6 substrate specificity at the P5 position and discovered that, similar to caspase 2, caspase 6 prefers pentapeptide substrates over tetrapeptides. Based on these data, we developed a set of chemical reagents for caspase 6 investigation, including coumarin-based fluorescent substrates, irreversible inhibitors and selective aggregation-induced emission luminogens (AIEgens). We showed that AIEgens are able to distinguish between caspase 3 and caspase 6 in vitro . Finally, we validated the efficiency and selectivity of the synthesized reagents by monitoring lamin A and PARP cleavage via mass cytometry and western blot analysis. We propose that our reagents may provide new research prospects for single-cell monitoring of caspase 6 activity to reveal its function in programmed cell death pathways.